An Accelerated, Practice-Based Model for Fostering Precepting Skills in Pharmacy Residents. Issue 8 (September 2014) - Anderegg, Sammuel V.; Christenson, Jay C.; Padgett, Carson P.
Sound precepting skills are vitally important for all pharmacists and for the future of our profession. Residency training provides a fertile environment for the resident to learn and foster new skills. This article outlines an accelerated model for developing precepting skills in residents and provides helpful advice for residents seeking to gain experience as a preceptor.